Postmedia and the Pedagogy of Videolanguaging - Bradley, Joff P. N.,; Grinberg, Silvia,; Iwase, Masayuki, (Educational Research E-Books Online, Collection 2026., 2025)
Are we forever trapped between reels and screens? Will robots, AI, and Big Data take over and dismantle education as we know it? Not at all! Postmedia and the Pedagogy of Videolanguaging presents alternatives to the now-common unthinking dystopias and the "systemic stupidity" that prevails and to which we seem doomed. The book creates a space for conceptual debates on the digital image-its power and heterogeneity-while offering practical pedagogical guidance on methods and techniques for reimagining and reclaiming pedagogy in a way that is fundamentally different, unique, and affirmative.